Coordinating chartist poetry: Past, present, future. Issue 5 (11th March 2020) - Sanders, Mike
Abstract: This article traces the development of the critical debate surrounding Chartist poetry with a particular focus on work from the last decade. It situates that critical work in relation to four key areas: its relationship to Chartist historiography, the implications of Romanticism as the dominant critical frame for discussions of Chartist poetry, its contribution to the wider field of Victorian Studies, and attempts to identify the esthetic specificity of Chartist writing. The article concludes by suggesting a number of areas for further study including discussions of the particular historical knowledge/evidence provided by Chartist poetry, the antecedents of Chartist poetry in the radical working‐class press of the 1820s and 1830s, its relationship to canonical Victorian poetry, and the elaboration of an appropriate set of esthetic criteria for Chartist poetry.